2011
DOI: 10.1192/pb.bp.110.032664
|View full text |Cite
|
Sign up to set email alerts
|

Gender reassignment: 5 years of referrals in Oxfordshire

Abstract: Aims and methodTo evaluate the characteristics of individuals seeking gender reassignment, the frequency of subsequent referrals to a specialist centre, and funding approval. Cases were identified from a local referrals database and data were extracted from case notes.ResultsFifty-four individuals attended for assessment; 70% were biological males and 30% were biological females. Mean age at referral was significantly different between the two groups. Over half were taking hormone supplementation and three had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(15 reference statements)
0
4
0
Order By: Relevance
“… 1 3 Five years ago, our group published a service evaluation of referrals to the adult (age 18 onwards) Oxford Gender Clinic between 2004 and 2009. 4 In this 5-year period, there were 56 referrals. We found levels of psychiatric morbidity to be lower than described in other samples, and there were significantly more individuals seeking male-to-female transition (70%) than female-to-male transition (30%).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“… 1 3 Five years ago, our group published a service evaluation of referrals to the adult (age 18 onwards) Oxford Gender Clinic between 2004 and 2009. 4 In this 5-year period, there were 56 referrals. We found levels of psychiatric morbidity to be lower than described in other samples, and there were significantly more individuals seeking male-to-female transition (70%) than female-to-male transition (30%).…”
mentioning
confidence: 97%
“…It has always been considered to be a rare disorder, but in recent years there has been an extraordinary increase in the number of referrals to both adult and child and adolescent gender clinics, with services becoming overwhelmed 1 3 . Five years ago, our group published a service evaluation of referrals to the adult (age 18 onwards) Oxford Gender Clinic between 2004 and 2009 4 . In this 5-year period, there were 56 referrals.…”
mentioning
confidence: 99%
“…Reports also exist of transgender individuals who seek dangerous underground alternatives such as unregulated hormone treatments or cheap surgery. For example, Saunders and Bass (2011) reported that of the transgender individuals they interviewed who were currently taking hormones, over half of them purchased the hormones from the Internet, thus potentially consuming unregulated medications and accepting the risk of dangerous side effects that are not properly monitored by a physician. One final consideration unique to Canadians is a large rural population, where geographical distance creates an additional barrier (after long wait times and high cost) to SRS access.…”
Section: Respect For the Dignity Of Personsmentioning
confidence: 99%
“…It is also important to note that transgender individuals often experience behavioral and emotional problems, including anxiety and depressive disorders, as a consequence of nonacceptance of their gender-variant behavior from others (APA, 2013). In one study of individuals who were assessed for SRS suitability, 24% had a current psychiatric disorder and 30% had a lifetime history of psychiatric disorder (Saunders & Bass, 2011). While psychiatric disorders do not necessarily affect capacity for consent, some conditions may impair decision-making ability.…”
Section: Respect For the Dignity Of Personsmentioning
confidence: 99%